Analysis of Haura Mart's Marketing Strategy Using the Marketing Mix Method and the SOAR in Dealing with the Competition - Sekar, Intan Ayu; Umam, Muhammad Isnaini Hadiyul; Lubis, Fitriani Surayya; Yola, Melfa; Hartati, Misra (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
This research to analyze the marketing strategy of Haura Mart supermarket in facing competition, namely by using the Marketing Mix (7P) method and the SOAR (Strengths, Opportunities, Aspirations, and Results) if you want to increase sales. Marketing Mix consists of Product, Price, Place, Promotion, Physical Evidence, People, and Process which are used to identify the most dominant factors in marketing objectives. while the SOAR method is the result of the analysis of the most dominant or influential factors of the marketing mix strategy (7P). The results of this study found that the most influential on the Marketing Mix method was from the results of the t-test, it was found that the factors that influenced sales volume were place with a t-value of 2.784, promotion with a t-value of 2.902, people with a t-value of 2.630, and process with a t-value of 2.133. This is because t-value > t-table (1.986). And SOAR calculations with the result of the total IFE matrix score is 3.518 and the total EFE matrix score is 3.737.So that the SA method, OA method, SR approach, and OR method marketing mixare the most effective strategies to increase Haura Mart supermarket sales in facing competition.